Menjelajahi Objek Wisata Lokal di Kota Kupang:Peran Video Podcast untuk Mahasiswa Bahasa Inggris Universitas Nusa Cendana - Novriani Rabeka Manafe; Gracia M. N. Otta; Elisna Huan (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This project aims to investigate the use of video podcasts by English students at Nusa Cendana University to explore local tourism objects in Kupang City. The study focuses on the student's engagement with video podcasts as a tool for understanding and promoting local tourism. The methodology mainly involved two procedures namely field trips to different tourism objects as well as creating video podcasts for promoting the destinations to the world. Field trips are an essential part of experiential learning and creating video podcasts allows students to develop cooperation and critical thinking along the process. The findings showed that 80 students divided into small groups explored natural spots such as beaches, a cliff, and bathing places. In addition, the students also dined at several culinary attractions. Next, they experienced going to the local museum as the historical venue. The results indicated that video podcasts are an effective means for English students to explore and showcase local tourism objects in Kupang City. The discussion highlights the potential of video podcasts in enhancing English language learning and promoting tourism.